Genetic correlations between dressage, show jumping and studbook‐entry inspection traits in a process of specialization in Dutch Warmblood horses. (27th September 2016) - Rovere, G.; Ducro, B.J.; van Arendonk, J.A.M.; Norberg, E.; Madsen, P.
Summary: Sport performance in dressage and show jumping are two important traits in the breeding goals of many studbooks. To determine the optimum selection scheme for jumping and dressage, knowledge is needed on the genetic correlation between both disciplines and between traits measured early in life and performance in competition in each discipline. This study aimed to estimate genetic parameters to support decision‐making on specialization of breeding horses for dressage and show jumping in Dutch warmblood horses. Genetic correlations between performance of horses in dressage and show jumping were estimated as well as the genetic correlation between traits recorded during studbook‐entry inspections and performance in dressage and show jumping competitions. The information on competition comprised the performance of 82 694 horses in dressage and 62 072 horses in show jumping, recorded in the period 1993–2012. For 26 056 horses, information was available for both disciplines. The information on traits recorded at studbook‐entry inspections comprised 62 628 horses, recorded in the period 1992–2013. Genetic parameters were estimated from the whole dataset and from a subset without horses recorded in both disciplines. Additionally, the genetic parameters were estimated in three different time periods defined by horses' birth year. The genetic correlation between dressage and show jumping in the whole dataset was −0.23, and it was −0.03 when it was estimated from horses recorded in only one discipline. The genetic correlation between dressage and show jumping was more negative in the most recent time period in all the cases. The more negative correlation between disciplines in more recent time periods was not reflected in changes in the correlations between competitions traits and the traits recorded in the studbook‐first inspection. These results suggest that a breeding programme under specialization might be most effective defining two separate aggregate breeding goals for each of the disciplines.